Synthesis and evaluation of swelling kinetics of electric field responsive poly(vinyl alcohol)‐g‐polyacrylic acid/OMNT nanocomposite hydrogels. Issue 1 (3rd February 2014) - Boruah, Monalisha; Mili, Medha; Sharma, Shyamalima; Gogoi, Biswajit; Kumar Dolui, Swapan
<x xml:space="preserve">Abstract</x> Novel electro‐responsive nanocomposite hydrogels were prepared by the radical graft polymerization reaction of partially neutralized acrylic acid on poly(vinyl alcohol) and organically modified MMT nanoclay (OMMT) using glutaraldehyde as a crosslinker and potassium initiator. The structures of the hydrogels were confirmed by using Fourier transform infrared, X‐ray diffraction, and scanning electron microscopy study. The nanocomposite hydrogels were characterized by evaluating such molecular weight between crosslinks, (Mc) crosslinking density (ρ), and mesh size (ξ). The effects of various parameters on the swelling behavior of the hydrogels were studied. The thermogravimetric analysis indicated that introduction of clay resulted in an increase in thermal stability. Finally, the electric stimuli responsive measurement indicates the bending of hydrogel toward the cathode in an aqueous solution of NaCl. POLYM. COMPOS., 36:34–41, 2015. © 2014 Society of Plastics Engineers